Perbedaan Kepuasan Terhadap Kualitas Pelayanan PT. X Yogyakarta Pada Nasabah Desa dan Nasabah Kota - Jati Pramono; Arundati Shinta; FX. Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2018)
Objective of this research is to understand the satisfaction difference between rural and urban customers toward the PT. X finance service. This customer’s satisfaction was very crucial point for service industry continuities such as bank and life insurance. Customer’s satisfaction was their main interest, since the satisfied customers would pass on their good comments to others. It was likely an informal advertisement but very powerful in influencing others. However, rural and urban customers presumably had different criteria on service quality. The hypothesis was that the rural customers were more likely to satisfy toward PT. X finance service quality than the urban customers were. The urban people were more likely to complain expressively about company’s service than the rural people were. The former customers also searched more on facilities such as bonuses and free opportunity to attend seminar about self-potential improvement. Forty customers participated in this research, 20 people had rural small industries and therefore they called as rural customers. The rest people had small industries in urban areas. We also used the Consumer’s Satisfaction Scale (71 items) as the main instrument to collect data. The scale consisted from five aspects i.e. product, price, place, promotion, and people. The validity score ranged from .226 - .838 and the reliability scores on each aspect respectively were acceptable i.e. .756, .930, .852, .851, and .920. This research revealed that there was significant difference between rural and urban satisfaction regarding the PT. X finance service quality (t = 2.416, p = .021 or p<.05). The rural people ( = 273.15) were more likely satisfy than urban customers do ( = 246.45). The rural people were more likely to continue their satisfied comments to their families and friends than the urban customers were. Higher appreciations toward the PT X’s staffs when serving customers were more prone from rural than urban costumers were. The urban people were more likely to make comparison among other similar finance enterprises. They were stricter on judging enterprise’s service quality. Apparently, many finance enterprises were more available in urban areas and they had tight competitions. In this research, we also suggested that the future researcher should invite the ex-customers to participate in this research. Those specific customers usually had rich dissatisfaction comments on enterprise’s service quality. Key words: Customer’s Satisfaction, Rural, Urban Customers.